Possible Protective Effects of Rebamipide, Tianeptine, Oleum Cinnamomi on Ethanol-Induced and Indomethacin-Induced Gastric Ulcer in Rats - Shahrazad Gazeti; Doaa Abdelmonsif; Amr Okda (AlQalam Journal of Medical and Applied Sciences, 2022)
Background and objectives. Peptic ulcer disease is a problem of the gastrointestinal tract characterized by mucosal damage secondary to pepsin and gastric acid secretion. It usually occurs in the stomach and proximal duodenum; less commonly it occurs in lower esophagus. The prominent causes are infection with Helicobacter pylori and the use of nonsteroidal anti-inflammatory drugs. This study was aimed to evaluate the possible protective effects of rebamipide, tianeptine, oleum cinnamomi on ethanol- and indomethacin-induced gastric ulcer. Methods. The present work was conducted on 72 male albino rats. Animals were randomly divided into 3 groups; Group I (8 rats), served as plain control group, they received 5 ml/kg body weight of 2% gum acacia orally daily for 7 days. Group II (32 rats), served as ethanol-induced gastric ulcer group. Group III (32 rats), served as indomethacin-induced gastric ulcer group. Results. In ethanol group; rebamipide treatment (II-b) resulted in a significant reduction in the ulcer score (P <0.001), Malondialdehyde content (P < 0.001) and Nuclear E2_releated factor2 content (P< 0.001). On the other hand, rebamipide produced an elevation of glutathione peroxidase activity (P<0.001), in ethanol control group. Tianeptine treatment (II-c) resulted in significant reduction in ulcer score P (<0.001), Malondialdehyde content (P < 0.001), Nuclear E2_releated factor2 content (P< 0.001), and an elevation of glutathione peroxidase activity with (P < 0.001) in ethanol group. Whereas, the Oleum Cinnamomi treatment resulted in significant reductions in ulcer score (P < 0.001), Malondialdehde content (P < 0.001), Nuclear E2_related E2 content (P< 0.001), and elevation in Superoxide dismutase activity content (P < 0.001) in ethanol control group. In indomethacin group; Rebamipide treatment (III-b) resulted in significant reductions in the ulcer score (P < 0.001) and Nuclear E2_related factor2 content (P < 0.001) in indomethacin control group respectively, while caused elevation in Superoxide dismutase, glutathione peroxides in indomethacin group respectively. Tianeptine treatment (III-c) resulted in significant reduction in the ulcer score (P < 0.001), Malondialdehyde content (P < 0.001) and Nuclear E2_ related factor content (P < 0.001) in indomethacin control group respectively; and an elevation in Superoxide dismutase, glutathione peroxidase activities in indomethacin control group respectively. Oleum Cinnamomi treatment (III-c) resulted in significant reduction in the ulcer score (P < 0.001), Malondialdehyde content (P < 0.001) and Nuclear E2_related factor2 content (P < 0.001) in indomethacin control group respectively; and an elevation in Superoxide dismutase, glutathione peroxidase activities in indomethacin control group respectively. Conclusion. Pretreatment for seven days with rebamipide, tianeptine, and cinnamon oleum, resulted in improvement in ulcer score, and gastric mucosal protection in rats with gastric ulcer induced by either in ethanol or indomethacin. This was associated with improvement in antioxidant parameters. Rebamipide produced the most prominent effect in ulcer score reduction.